2020
DOI: 10.3233/jad-191011
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Stroke Prevention After Ischemic Stroke in Patients with Alzheimer’s Disease and Other Dementia Disorders

Abstract: Background: Recurrent ischemic stroke (IS) increases the risk of cognitive decline. To lower the risk of recurrent IS, secondary prevention is essential. Objective: Our aim was to compare post-discharge secondary IS prevention and its maintenance up to 3 years after first IS in patients with and without Alzheimer's disease and other dementia disorders. Methods: Prospective open-cohort study 2007-2014 from the Swedish national dementia registry (SveDem) and the Swedish national stroke registry (Riksstroke). Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Stroke detection may be delayed in patients with dementia, missing the window for acute reperfusion treatments. These treatments may be withheld in patients with reduced life expectancy [ 14 ]. Nevertheless, during the study time period, utilization of stroke alarm increased in both groups and the differences between its use in patients with and without dementia disappeared.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stroke detection may be delayed in patients with dementia, missing the window for acute reperfusion treatments. These treatments may be withheld in patients with reduced life expectancy [ 14 ]. Nevertheless, during the study time period, utilization of stroke alarm increased in both groups and the differences between its use in patients with and without dementia disappeared.…”
Section: Discussionmentioning
confidence: 99%
“…In our prior study, performed in a similar population, pre-stroke dementia was associated with excess mortality risk 3 months after stroke; however, this was partially mediated by poorer pre-stroke mobility [ 13 ]. Another possible explanation for increased mortality could be the higher occurrence of cardioembolic strokes in patients with dementia due to underutilization of anticoagulation in patients with dementia and atrial fibrillation (AF), as these strokes are more severe [ 14–17 ]. Even though intravenous thrombolysis and mechanical thrombectomy have lower population benefits (lives saved from death or dependency) than, e.g., hospitalization in a stroke unit or pharmacological prevention [ 18 ], lower utilization of these in patients with dementia [ 19 ] could lead to worse outcomes and worse survival.…”
Section: Introductionmentioning
confidence: 99%
“…15 However, they found that the use of drugs from any particular class did not differ between the 2 groups, which is similar to our findings. More recently, Zupanic et al 13 examined data in the Swedish National Dementia Registry and found that compared with adults without dementia, adults with dementia were less likely to be prescribed statins, antihypertensive medications, and anticoagulants during the 3 years after their first ischemic stroke associated with atrial fibrillation. Although their findings were not consistent with ours, they conducted the study using data obtained outside the US, and the inconsistency might be attributable to differences in health care systems or culture.…”
Section: Jama Network Open | Health Policymentioning
confidence: 99%
“…Thus, adults with dementia may be receiving a poorer quality of chronic disease management than those without dementia. However, existing studies [7][8][9][10][11][12][13] are limited to those conducted outside the US, those based on data obtained from limited regions in the US, 14,15 or those restricted to nursing home residents [16][17][18] ; therefore, the association of dementia status with the quality of chronic disease management among community-dwelling individuals in the US at the national level is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…A relevant number of elderly persons affected by AD report comorbidities, mostly cardiovascular conditions and/or diabetes. Vascular and thrombotic risk factors (i.e., hypertension, diabetes, and hyperlipidemia) have also been described as potentially associated with an increased risk and progression of cognitive decline in AD and vascular and mixed dementia [5]. Depending upon the disease severity, stroke is three-to-seven times more common in these patients, and the cerebrovascular lesions may lower the threshold for clinical manifestation of AD.…”
Section: Introductionmentioning
confidence: 99%